Math Problem Statement

¬(pq)↔(p∧¬q)

Solution

The given logical expression is:

¬(pq)(p¬q)\neg(p \rightarrow q) \leftrightarrow (p \land \neg q)

Let's break it down:

Left Side: ¬(pq)\neg(p \rightarrow q)

The negation of pqp \rightarrow q can be rewritten using logical equivalences:

  • pqp \rightarrow q is equivalent to ¬pq\neg p \lor q.
  • So, ¬(pq)\neg(p \rightarrow q) is equivalent to ¬(¬pq)\neg(\neg p \lor q).

Using De Morgan's law, we can simplify:

¬(¬pq)p¬q\neg(\neg p \lor q) \equiv p \land \neg q

Right Side: p¬qp \land \neg q

This is already in its simplest form.

Final Expression:

Thus, ¬(pq)\neg(p \rightarrow q) simplifies to p¬qp \land \neg q, and the given expression:

¬(pq)(p¬q)\neg(p \rightarrow q) \leftrightarrow (p \land \neg q)

is always true, since both sides are logically equivalent.

Conclusion:

The logical biconditional (↔) holds because both sides represent the same logical statement.


Would you like further details on this or have any specific questions?

Here are 5 questions to expand on the topic:

  1. What are the truth tables for pqp \rightarrow q and ¬(pq)\neg(p \rightarrow q)?
  2. How does De Morgan’s law apply in propositional logic?
  3. What is the relationship between conjunction (∧) and disjunction (∨)?
  4. Can you explain the conditions under which a biconditional (↔) holds true?
  5. How does negating an implication affect its truth value?

Tip: Understanding logical equivalences helps simplify complex propositions easily.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Propositional Logic
Logical Equivalences
Negation
Biconditional

Formulas

Implication: p → q ≡ ¬p ∨ q
Negation of implication: ¬(p → q) ≡ p ∧ ¬q
De Morgan's Law: ¬(¬p ∨ q) ≡ p ∧ ¬q

Theorems

De Morgan's Law
Biconditional Truth

Suitable Grade Level

Undergraduate / Advanced High School (Grades 11-12)